APLIKASI BIOMATERIAL DALAM KARDIOLOGI: STENT KORONARIA - Nasution, Ahmad Kafrawi (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2012)
Research in the field of materials has become widespread. Biomaterials is a term that is aimed at material that is part of medical implants. Biomaterials have been used by humans both to improve appearance and restore organ function. Modern biomaterials are still needed and biofunctionality study of biocompatibility of implants. Biocompatibility must be referring to the material properties to be safe and work in harmony with the body without causing other harmful effects. An important aspect to consider from the biocompatibility of products starting from the fabrication process, corrosion resistance and modification of implant materials and coatings.